SYSTEM ANALYSIS AND COMPUTER SOFTWARE IN THE DESIGN OF OPTIMIZATION OF ENGINEERING STRUCTURES AND STRUCTURES - Xoliyorova , Khilola Komilkizi (Sanoatda raqamli texnologiyalar, 2024)
This article discusses the design processes of mechanical engineering products according to specified criteria. For fast and high-quality product development, a comprehensive analysis and calculation of the designed object at the development stage is required. The first design task is to develop the correct engineering solution to ensure that the product performs its functions. To find the only final result, it is necessary to make a decision from a set of alternative solutions. Thus, obtained on the basis of models of intelligent decision support, the process of designing machine-building products in CAD is provided with information. For this, first of all, it is necessary to analyze the existing types of CAD systems and determine the possibility of increasing the intelligence of their subsystems.